1999
DOI: 10.1034/j.1399-3054.1999.105120.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial regulation of the expression of 1‐aminocyclopropane‐1‐carboxylate oxidase by ethylene in mung bean (Vigna radiata)

Abstract: Ethylene induced an increase in the level of 1‐aminocyclopropane‐1‐carboxylate oxidase (VR‐ACO1) transcript in mung bean hypocotyls. Time course study revealed that the level of the VR‐ACO1 mRNA in excised mung bean hypocotyls increased after 2‐h ethylene treatment and much higher mRNA levels were observed thereafter, while the basal level of transcript was slightly decreased in control tissues. The in vivo ACC oxidase activity increased from 31 nl g−1 h−1 at zero time to maximum activity of 62 nl g−1 h−1 at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
(40 reference statements)
2
14
0
Order By: Relevance
“…The results described in Figure 4, as well as those from previous studies (Kim and Yang, 1994;Jin et al, 1999) clearly demonstrate that the level of VR-AC01 transcript markedly increases in response to ethylene in mung bean hypocotyl tissue. However, we still could not determine whether ethylene induced gene expression at either the transcriptional or the posttranscriptional level.…”
Section: Nuclear Run-on Transcription Assaysupporting
confidence: 78%
See 2 more Smart Citations
“…The results described in Figure 4, as well as those from previous studies (Kim and Yang, 1994;Jin et al, 1999) clearly demonstrate that the level of VR-AC01 transcript markedly increases in response to ethylene in mung bean hypocotyl tissue. However, we still could not determine whether ethylene induced gene expression at either the transcriptional or the posttranscriptional level.…”
Section: Nuclear Run-on Transcription Assaysupporting
confidence: 78%
“…These results indicate that ethylene is closely associated with the induction of the ACC oxidase gene in fruit tissues. We previously showed that ethylene markedly stimulated the accumulation of ACC oxidase mRNA in mung bean hypocotyls, and suggested that ethylene plays an important role in regulating ACC oxidase gene expression in vegetative mung bean hypocotyl tissue, as it does in fruit tissues (Kim and Yang, 1994;Kim et al, 1997a;Jin et al, 1999). From these results, we might infer that the low, basal level of ACC oxidase transcript constitutively expressed in mung bean hypocotyls is regulated by the endogenous ethylene present in those tissues.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Previously, we showed that ethylene markedly stimulated the accumulation of ACC oxidase mRNA in vegetative tissues of mung bean (Kim and Yang, 1994;Jung et al, 2000) and tobacco plants. Based on these results, it has been proposed that ethylene plays a key role in regulating ACC oxidase gene expression in vegetative tissues, as it does in fruit tissue, and that the low basal level of ACC oxidase transcript constitutively expressed in vegetative tissues is regulated by the endogenous ethylene present in these tissues (Kim et al, 1997;Jin et al, 1999). This autocatalysis reaction by ethylene results from the transcriptional activation of the ACC oxidase gene (Park et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNAs of mung bean and tobacco plants were obtained by a method adapted from the established protocols reviewed by Lizzradi (1983) with modifications as described previously by Jin et al (1999). The total RNAs were precipitated overnight at 4°C by the addition of 0.3 vol of 10 m LiCl and then precipitated in ethanol.…”
Section: Rna Isolation and Northern-blot Analysismentioning
confidence: 99%